Creep from the deep - Stine, R. L. (New York : Scholastic, 2008)
Billy and Sheena have a deep-sea encounter with a dead captain and the terrifying adventure continues when they arrive in HorrorLand, a place where nightmares come true.
Creep from the deep -- Enter HorrorLand -- Fear file.
3.4
5-8
5-8
Keywords: Amusement parks -- Juvenile fiction; Nightmares -- Juvenile fiction; Amusement parks -- Fiction; Horror stories; Nightmares -- Fiction; Amusement parks -- Fiction; Dreams -- Fiction; Horror fiction; Horror fiction